Mental health Profiles of Sexually Abused Youth: Comorbidity, Resilience and Complex PTSD - Alie-Poirier, Alexane; Hébert, Martine; McDuff, Pierre; Daigneault, Isabelle (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Objectives: The current study’s objectives were to 1) determine if sexually abused youth in child protective agencies (CPA) were given more psychiatric diagnoses and exhibited more comorbidity than youth from the general population, 2) examine the comorbidity profiles of sexually abused youth over 10 years of medical consultations and hospitalizations.Method: Diagnoses of 882 youth with a substantiated sexual abuse report between 2001 and 2010 at a participating CPA were compared to those of 882 matched controls (n = 1764).Results: Results of generalized linear mixed models showed that sexually abused youth presented higher rates of all diagnostic categories and were up to four times more likely to present comorbid diagnoses. Latent class analyses among abused youth revealed four different comorbidity profiles; two more severe groups named complex trauma (11%) and dissociation (14%); and two less severe groups named depression (10%) and low or no comorbidity/resilience (65%). Youth with more cumulative maltreatment and greater number of years of data following CSA report were more at risk of presenting a comorbidity profile, while females were more likely to present a depression profile. Profiles of youth in the highest comorbidity class were similar to what is defined as complex trauma or complex post-traumatic stress disorder.Implications: Sexually abused youth's varied profiles warrant varied interventions. Integrated trauma informed interventions are needed to address the cumulative maltreatment experienced and the psychiatric comorbidity some youth exhibit.